A legitimidade do processo de formação das leis pela participação da sociedade civil: a comissão de legislação participativa - Seleghim, Ariane Duarte (2015)
Habermas’ contemporary democratic theory brings a very important question regarding to the formation of laws and its legitimacy: beyond the formal procedure previously established for the construction of the fundamental normative outline to the Democratic Rule-of-Law State (Weber’s instrumental rationality), the institutional engineering focused on the law formation shows itself compromised only with the democratic systematic, when it observes the “practical-moral reasoning”, which proposes the forecasting of the moral argumentative procedures of those possible affected by the rule, within the production process of the legal rules. This is about the necessity of permeability of the legislative process to demands and pleas from civil society. The Participative Rule Committee, institutionalized instrument of promotion of this permeability: receives suggestions and demands from civil society, converting them into bills. Observing the demands received by the committee, it was possible to conclude that civil society took its place in the institutionalized participation and more: that the demand for more participation in law formation (public hearings) increased more and more.